Confessional Policy of Russia of the XIX Century Regarding the Muslim Belief Confession of the Peoples of the North Caucasus (Global Journal of Human-Social Science, 2019)
The publication analyzes the confessional policy of the Russian Empire, which it conducted in the 19th century in the North Caucasus. On the basis of archival and documentary materials, it is proved that the Russian state favored Muslims, which speaks of the Islamic Renaissance, which included: the legitimization of traditional Islamic institutions and their functioning, the establishment of mosques during which religious studies were conducted. It is concluded that the socio-spiritual modernization developed by the Russian Empire in the North Caucasus in the 19th century contributed to the consolidation of Islamic religion in the mountain environment. However, many projects of the ongoing reform turned out to be imperfect, and therefore to this day generate controversy not only among Russian politicians, but also among foreign political scientists. In this context, this publication may be useful not only to Russian, but also to foreign researchers in developing balanced diplomacy in solving Muslim problems.
Keywords: russian state; north caucasus region; reform; islamic renaissance; foreign ethnic society